In vitro 3D drug sensitivity testing for patient-derived tumor-like cell clusters and whole-exome sequencing to personalize postoperative treatment: A study protocol for a multicenter randomized controlled trial. - Xiaoyuan Qiu; Ruiqiang Li; Gengchen Xie; Ning Ning; Zhenjun Wang; Jiaolin Zhou; Ge Liu; Qingchao Tang; Zhuo He; Leilei Yang; Junyang Lu; Peng Li; et al. (PLoS ONE, 2025)
Background Colorectal cancer (CRC) ranks as the third most common cancer globally, with significant postoperative recurrence and metastasis rates. The heterogeneity of CRC presents challenges in the selection of adjuvant chemotherapy regimens, highlighting the need for personalized treatment strategies. The development of in vitro models for drug sensitivity testing, including a novel patient-derived tumor-like cell cluster (PTC) model, offers a potential solution for predicting drug efficacy and guiding treatment. Methods and design This multicenter randomized controlled trial (RCT) aims to evaluate the consistency between the in vitro PTC drug sensitivity test results with whole exome sequencing and the clinical prognosis of CRC patients. The study will involve 200 patients who will be randomly assigned to receive either PTC-guided adjuvant chemotherapy or traditional chemotherapy. The primary endpoint is the 3-year disease-free survival rate (3yDFS), with secondary endpoints including the consistency between test results and clinical outcomes and the prognostic value of gene mutations and other biomarkers. Discussion This study represents a significant step toward precision medicine in CRC treatment by integrating PTC technology with whole-exome sequencing. These findings could provide valuable insights into personalized treatment approaches, potentially improving the clinical outcomes of patients with CRC. Trial registration ClinicalTrials.gov: NCT05424692. Registered on June 21, 2022.